IMPLEMENTASI EDUKASI MEDIA PPT INTERAKTIF UNTUK MENGENALKAN KONSEP DASAR LITERASI KEUANGAN PADA AUD DI KB ANGGREK LANDUNGSARI - Syaikha, Rafa Zahra; Tuffahati, Rafsya Shakilla; Nailu Rakhmah, Zahrotun Nisa; Nur Khasanah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to explain the implementation of interactive PowerPoint (PPT) media as an educational tool to introduce basic financial literacy concepts to early childhood students at KB Anggrek Landungsari. The research is motivated by the critical need to instill financial awareness from an early age to shape children’s character by helping them distinguish between wants and needs. Using a descriptive qualitative method, data were collected through observation, interviews, and documentation. The interactive PPT media was designed with animated visuals, currency-recognition games, and savings simulations tailored to the developmental stages of young children. Findings indicate that the implementation of this interactive media significantly increased student engagement and understanding compared to conventional methods. Students demonstrated an improved ability to identify currency values and grasp the importance of saving through engaging simulations. In conclusion, the use of interactive PPT is an effective pedagogical strategy for simplifying abstract financial concepts into concrete experiences for early childhood. This technology-based approach serves as a valuable reference for educators in developing innovative and practical learning tools